2003
DOI: 10.1590/s0103-97332003000400036
|View full text |Cite
|
Sign up to set email alerts
|

Ghost free analysis of a nonsymmetric theory of gravitation

Abstract: The absence of ghost-negative energy radiative modes in a proposed generalized theory of gravitation based on a non-symmetric metric is reanalyzed. The missing contribution of the symmetric sector of the Lagrangian is calculated and shown to be null. The ghost free character of the theory is then firmly established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The theory was shown to be consistent with the four classical tests of general relativity (GR). In [2] it was shown that the theory is definitely free of ghost-negative radiative modes even when expanded around a Riemannian GR background space. In a more recent paper [3] the conservation laws of energy and momentum were established.…”
Section: Introductionmentioning
confidence: 99%
“…The theory was shown to be consistent with the four classical tests of general relativity (GR). In [2] it was shown that the theory is definitely free of ghost-negative radiative modes even when expanded around a Riemannian GR background space. In a more recent paper [3] the conservation laws of energy and momentum were established.…”
Section: Introductionmentioning
confidence: 99%